Gambaran E-learning Readiness pada Mahasiswa Unika Atma Jaya selama Masa Pandemi COVID-19 - Carla Dominica Gabriella; Margaretha Purwanti; Aireen Rhammy Kinara Aisyah (MANASA, 2022)
The Covid-19 pandemic has undoubtedly had quite a significant impact on many aspects of human society, including a students’ learning experiences. As of March 2020, in lieu of recent policies to mitigate the spread of Covid-19, all institutions in Indonesia have been required to do distance learning, including universities. This sudden change could possibly have an impact on the learning process on a student’s learning. Seeing as most universities use E-Learning as the preferred method of distance learning, this study aims to study the readiness of students to participate in E-Learning. This study uses a quantitative descriptive method to analyse the E-Learning Readiness (ELR) of Faculty of Psychology students from Unika Atma Jaya from batches 2018-2021. This study involves 180 participants aged 17-24. Analysis shows that generally students are ready to use E-Learning (ELR score = 3,5 where above 3,4 is considered ready, but not optimal), specifically in the dimensions Learner Control and Motivation For Learning. When further broken into two groups 2018-2019 (experienced face to face before pandemic) and 2020-2021 (E-Learning only), 2018-2019 students show a trend of having lesser readiness levels than their 2020-2021 peers. Even if according to t-score analysis shows no statistical difference between the overall ELR levels of students in batches 2018-2019 and 2020-2021, there are still differences in ELR scores when analysing individual dimensions, particularly the dimensions Computer Internet Self-Efficacy, Motivation For Learning, and Learner Control.